Conventionalised Impoliteness towards Perceived ESL Users on 4chan - Rosli, Mohamad Ammar (Journal of Modern Languages, 2018)
Siegel (2018) suggests that language can be used as an identity marker for an individual. This seems to be the case on 4chan, an anonymous image board where certain users are labelled as ‘ESL’ even though there are no information regarding their ethnicity, nationality, or languages spoken. Users who are perceived to be incompetent in English are labelled with the term and are usually discriminated against through the use of impoliteness. Analysis of the data shows that different categories of impoliteness are used against perceived ESL users to isolate, exclude and mock them. It is also shown that the phenomenon studied could be regarded as a form of language based discrimination, as perceived ESL users are identified and singled out by 4chan users based on language.